Return-to-work interventions for persons/employees with mental illnesses. Issue 4 (9th July 2022) - Hamann, Johannes; Lang, Anne; Riedl, Lina; Brieger, Peter
Abstract : Purpose of review: Mental illnesses are among the most common diseases worldwide. Cases of inability to work caused by mental illness are frequent and the related economic burden is immense. A successful reintegration into their work environment of those patients who were on sick leave due to a mental illness is an important prognostic factor for the further course of the disease and helps reducing financial consequences. It was the aim of the present review to give an overview of the status quo of return-to-work interventions in the international literature. Recent findings: Main themes of interventions addressing return to work of persons with mental illnesses are the provision of psychotherapeutic support with or without combining these approaches with work directed interventions. Personal contact of employees, mental healthcare staff and supervisors may be helpful with regard to facilitating return to work. Summary: Current return to work interventions are mostly elaborate, extensive and expensive without convincing results regarding work related outcome parameters. A variety of reasons might be responsible for this finding, including heterogeneity of outcomes, a poor definition of return-to-work-interventions and the complexity of the issue (involving multiple stakeholders).